Fatkullina imitata n. sp., second species of a unique cheilostome bryozoan genus with reversed-polarity zooidal budding, and new family Fatkullinidae - Grischenko, Andrei V.; Gordon, Dennis P.; Morozov, Taras B. (Zootaxa, 2018)
A second species of the unique cheilostome bryozoan genus Fatkullina, with reversed-polarity zooidal budding, has been discovered. Fatkullina imitata n. sp. is described from the western Kamchatka shelf and upper slope of the Sea of Okhotsk. It differs from the type species, F. paradoxa, by the combination of orificial characters, the convex distal third of the frontal shield, and predominantly crimson coloration of dry colonies. A new family, Fatkullinidae, is erected to accommodate Fatkullina (as the type genus) and also Stomacrustula, Pachyegis and Lepralioides. The origin of reversed polarity zooidal budding is considered to arise as a consequence of the unique T-shaped geometry of the ancestrula and transverse daughter zooid followed by spiral budding of periancestrular and succeeding generations of zooids within the zone of astogenetic change.